2015
DOI: 10.1002/ajh.24011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone marrow reticulin in patients with chronic immune thrombocytopenia treated with eltrombopag: Data from the EXTEND study

Abstract: Thrombopoietin receptor agonists, which raise platelet counts in patients with chronic immune thrombocytopenia, may be associated with increases in bone marrow (BM) reticulin. Patients with chronic immune thrombocytopenia participating in the Eltrombopag Extended Dosing (EXTEND) study underwent BM biopsies to identify clinically relevant BM fibrosis‐related increases. Specimens were centrally reviewed by 2 hematopathologists. Two hundred thirty‐two biopsy specimens were collected from 117 patients treated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 13 publications
4
41
0
2
Order By: Relevance
“…The Eltrombopag Extended Dosing Study (EXTEND), which started in 2006, is a recently completed, open-label trial that assessed adult patients with chronic ITP who were being treated with eltrombopag for bone marrow reticulin fibrosis. 31 Initial results from this trial were published in 2015 and showed moderate to marked fibrosis in only 2 patients. 31 One patient's marrow findings reversed after the patient withdrew from the study.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Eltrombopag Extended Dosing Study (EXTEND), which started in 2006, is a recently completed, open-label trial that assessed adult patients with chronic ITP who were being treated with eltrombopag for bone marrow reticulin fibrosis. 31 Initial results from this trial were published in 2015 and showed moderate to marked fibrosis in only 2 patients. 31 One patient's marrow findings reversed after the patient withdrew from the study.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…31 Initial results from this trial were published in 2015 and showed moderate to marked fibrosis in only 2 patients. 31 One patient's marrow findings reversed after the patient withdrew from the study. 31 The final results of the study (published in December 2017) showed data from 356 biopsy specimens collected from 166 patients treated for up to 7 years with eltrombopag.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…The distinction between bone marrow samples in early MDS and ITP may be difficult. Abnormal megakaryocyte morphology and, sometimes, fine fibres of reticulin deposits can be observed in ITP (Brynes et al, 2015;Rivi ere et al, 2015). A frequent situation is the presence of some features of dyserythropoiesisis and/or dysgranulopoiesis in the blood smear, which are insufficient to ascertain MDS (<10% dysplasia of myeloid lineage and blast proportion <5%), sometimes considered to be idiopathic cytopenia of undetermined significance (ICUS) (Valent et al, 2012;Kwok et al, 2015).…”
Section: How Is Itp Diagnosed In the Elderly?mentioning
confidence: 99%
“…The most concerning side effects are thrombocytosis, thrombosis, transaminitis with eltrombopag, and bone marrow reticulin changes. [38][39][40] Eltrombopag was associated with cataract formation in early preclinical studies; however, in clinical trials the risk does not appear to be increased. It is unclear whether any additional risks would be increased with concomitant corticosteroid use or any new safety signals will be discovered.…”
Section: Thrombopoietin-receptor Agonistsmentioning
confidence: 99%